Satirical Style in the Story of Qaryat Al-Hukama by Abdul Aziz Muhammad: An Analytical Study of Social Function Theory - Waluyo, Azriel Shabrina Djenar; Rosanti, Mita; Fitriyah, Safira Hasna (Proceedings of International Conference on Islamic Civilization and Humanities, 2026)
Satire is a form of figurative language in literary works used to satirize or criticize various weaknesses, stupidity, or deviations in the lives of individuals or society. In its use, satire is often subtly packaged through humor, irony, or sarcasm so that the critical message is easily understood by the reader without being overly harsh. The story "Qaryat al-Hukama'" by Abdul Aziz Muhammad depicts social values ​​that can be analyzed through the use of satirical style in the plot.This study aims to analyze the use of satirical style in the story "Qaryat al-Hukama'" and explain its social meaning. This study used a qualitative descriptive method with a social function approach to literature. The research data consisted of text excerpts from the story "Qaryat al-Hukama'" that demonstrate satirical elements.The results show that the satirical style in the story is displayed through ironic situations and depictions of social conditions that define human life based on work activities. Through this use of satirical style, the story conveys both social criticism and a moral message regarding the importance of work and the role of individuals in society